Modified Penicillin Enrichment Procedure for the Selection of Bacterial Mutants - Fitzgerald, George (1975)
Penicillin enrichment and selection of biochemical mutants was performed on agar plates. With this technique, there is an optimum penicillin exposure time for the greatest yield of a particular auxotroph.